2010
DOI: 10.1108/14777281011019452
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing organizational recovery in tough times: a pragmatic perspective

Abstract: PurposeThe purpose of this paper is to offer possible perspectives on pursuing organizational recovery given the current level of intensity in the global economic environment.Design/methodology/approachThe suggested approaches offered in this article are presented from a pragmatic perspective. While empirical support for these approaches can be found in the literature, some of the conclusions drawn in the paper were not validated empirically.FindingsLeaders and managers could easily become discouraged by the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…They highlight that companies that build capital by sharing knowledge and learning from each other will be able to better minimize outside disruption to the organization. In times of organizational strife and disruption, the frustration and anxiety felt by organizational members also increases [77], and frustration and anxiety in turn may lead to collective employee turnover [78]. Regardless of the origin of organizational member withdrawal, lesser organizational interactions can stifle the social networks that sustain the organization.…”
Section: Discussion and Practical Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…They highlight that companies that build capital by sharing knowledge and learning from each other will be able to better minimize outside disruption to the organization. In times of organizational strife and disruption, the frustration and anxiety felt by organizational members also increases [77], and frustration and anxiety in turn may lead to collective employee turnover [78]. Regardless of the origin of organizational member withdrawal, lesser organizational interactions can stifle the social networks that sustain the organization.…”
Section: Discussion and Practical Insightsmentioning
confidence: 99%
“…Regardless of the origin of organizational member withdrawal, lesser organizational interactions can stifle the social networks that sustain the organization. This is possibly because critical information about internal activities cannot be shared with others in the organization [77]. Therefore, good organizational communication helps to restore and strengthen organizational relationships, reshape the organization's social network, and enable knowledge sharing and exchange with other members of the organization, thereby enhancing the organization's ability to cope with crises and increase organizational resilience.…”
Section: Discussion and Practical Insightsmentioning
confidence: 99%
“…First, as there has been no systematic research approach, there has been little consistency in the measurement of the dimensions associated with organizational resilience. Second, while some studies have sporadically explored organizational resources [20], organizational communication, and team relationships as possible influencing factors, few studies have systematically summarized or analyzed the influencing factors, the action mechanisms associated with organizational toughness, or the importance of the influencing factors over time. While some studies have examined tourist organizations' resilience, there has been no consensus on the conceptualization or operationalization of the resilience concept.…”
Section: Organizational Resiliencementioning
confidence: 99%
“…Second, the organizational behavior perspective mainly includes organizational communication and organizational change. Schraeder & Hoover (2010) [12] state that intraorganizational communication facilitates knowledge sharing among organizational members, eliminates conflict among organizational members, and enhances organizational cohesion, thereby improving the organization's ability to cope with crises. Lengnick-Hall et al (2011) [14] state that in a volatile, everchanging marketplace, only flexible and changing organizations can thrive, and that organizational change facilitates organizations to maintain positive alignment under challenging conditions and customer service severe reconciliation, thus enhancing the organization's ability to respond to crises, while at the same time, organizational learning facilitates the development of dynamic capabilities that promote organizational change [70].…”
Section: ) Organizational Levelmentioning
confidence: 99%
“…Due to the differences in research fields and disciplinary classifications, scholars have different understandings of the connotation of organizational resilience, resulting in no mature and authoritative assertions on organizational resilience in terms of dimensions and measurements. At the level of influencing factors, both studies have fragmentedly explored the effects of self-esteem [4], At the level of influencing factors, some studies have sporadically explored the effects of organizational communication [12] and organizational resources [13] on organizational resilience, but no scholars have systematically summarized and analyzed the influencing factors of organizational resilience and the relationships among the influencing factors; at the level of mechanism of action and effect, some studies have explored the effects of organizational resilience on organizational In terms of mechanisms of action and effects, some studies have explored the effects of organizational resilience on organizational competence [14], organizational evolution [6], and corporate success [15], but few studies have revealed the mechanisms of action of organizational resilience from a systemic perspective.…”
Section: Introductionmentioning
confidence: 99%